Herbal Extract Diminishes Diclofenac-Induced Nephrotoxicity - Etab Abdul-Ameer AL-Ogla; Huda N. AL-baroody; Mohanad Yahya Al-Mhanna; Hadeel Khalaf Alboaklah (Universitas Muhammadiyah Sidoarjo, 2026)
Nonsteroidal Anti-Inflammatory Medications (NSAIDs) are among the most frequently recommended painkillers, and their renal toxicity effects are predictable. Numerous studies have shown a link between the development of advanced-stage chronic kidney disease (CKD) and high doses of NSAID exposure and frequently prescribed medications that make up 5–10% of all prescriptions written in the US. Diclofenac (DFC) is widely used as an analgesic and anti-inflammatory agent. The use of medicinal plants is a new strategy to mitigate the adverse effects of other medications. Artemisinin has now led to the development of vital antimalarial medications for the increasingly prevalent therapy-resistant malaria strains. While Artemisinin was primarily used to treat malaria, numerous subsequent studies have confirmed that it has additional pharmacological functions, including antitumor, antiarrhythmic, and antifibrotic effects. This study aimed to examine the capacity of Artemisinin to reduce (DFC) and to stimulate hepatic and renal toxicity in a rat model.DFC was injected intramuscularly twice daily for seven days, and Artemisinin was administered by oral gavage for the same time. Hematological and biochemical profiles were analyzed. Tissue damage was assessed under microscopy and histopathological reporting. DFC administration produced renal and hepatic function test abnormalities and decreased hematocrit and hemoglobin values, but increased WBC and platelet counts. Histopathological examination revealed renal tubular injury, hepatocyte injury, and increased fibrosis in the DFC rat group. Artemisinin administration, in addition to DFC treatment, reduced hematological test irregularities and DFC, thereby causing renal functional damage, as evidenced by a marked increase in serum creatinine and uremia levels.